Pengembangan unit wirausaha mahasiswa dan masyarakat melalui kegiatan PPUPIK Sarabba Instan - Halimah Husain; Muhammad Junda; Nur Raisah Maddeppungeng; Nurasmi Nurasmi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This program aims to create access to the creation ofnew entrepreneurs by developing / training students to haveproduction process skills in the field of healthy food chemistryand chemistry and having the skills to run businesses based onlocal food products. The program also aims to encourage thedevelopment of lecturer and student research results to beutilized and socialized. One of the products produced in thisprogram is Sarabba Instan. Sarabba Instan is a traditionalBugis-Makassar health drink made from ginger Enrekang.Instant Sarabba is made through several stages of production,namely stripping, drying, extracting ginger juice, stirring, anddrying. In this program, the production of instant sarabba iscarried out until the taste and processing are stable with theselection of quality basic ingredients. Organoleptic testing isdone to determine the level of consumer preference for InstantSarabba. Organoleptic testing was carried out by panelistsfrom several circles on campus, namely lecturers, staff, andstudents. The results showed that the three groups likedSarabba Instan with a percentage of preference of 90.91%,85.72%, and 66.68% respectively for lecturers, employees, andstudents. Sarabba Instan is a superior food innovation productbecause of its more practical and healthy presentation. TheSarabba Instan PPUPIK program is an instant productioncenter for Sarabba conducting Training, Seminar workshops,entrepreneurial exhibitions for students who have and want torun a business and community who need coaching.